Effectiveness of the BBV-152 and AZD1222 vaccines among adult patients hospitalized in tertiary hospitals in Odisha with symptomatic respiratory diseases: A test-negative case–control study - Bhattacharya, Debdutta; Kanungo, Srikanta; Palo, Subrata Kumar; Kshatri, Jaya Singh; Pattnaik, Matrujyoti; Ghosal, Shishirendu; Mohapatra, Pranab; Rao, C. Mohan; Sahoo, Avinav; Mishra, Rudra Prasanna; Mishra, Sanghamitra; Mohanta, Amiya Ranjan; et al. (Frontiers in Public Health, 2023)
Two vaccines, namely BBV-152 (COVAXIN®) and AZD1222 (COVISHIELD™), were deployed against SARS-CoV-2 in India from January 16, 2021. Frontline health care workers were vaccinated first, followed by the adult population. However, limited data on vaccine effectiveness are available for the population of India. Therefore, we aimed to evaluate the effectiveness of two doses of each of these two common vaccines against COVID-19 infection among hospitalized patients with pulmonary conditions. We adopted a test-negative case–control design and recruited a sample of adults who were admitted to one of six tertiary care hospitals in Odisha. All participants were hospitalized patients with COVID-19-like pulmonary signs and symptoms. Participants who tested positive for SARS CoV-2 via RT-PCR were treated as cases, and those who tested negative were treated as controls. Logistic regression, adjusted for participants' age, sex, and number of comorbidities, was used to calculate the effectiveness of the two vaccines, using the formula: 100*(1 – adjusted odds ratio). Between March and July of 2021, data were collected from 1,614 eligible adults (864 cases and 750 controls). Among all participants, 9.7% had received two doses of one of the two COVID-19 vaccines. Vaccine effectiveness was 74.0% (50.5%−86.0%) for two doses of BBV-152 and 79.0% (65.4%−87.2%) for two doses of AZD1222. Thus, two doses of either BBV-152 or AZD1222 nCoV-19 vaccine were found to be substantially effective in protecting against COVID-19-related infection.